ISU DAN TANTANGAN DALAM PENGIMPLEMENTASIAN PROGRAM JAMINAN KESEHATAN DI INDONESIA - Rachmad Miftachul Arifuddin (JAMER : Jurnal Akuntansi Merdeka, 2022)
There is evidence that the existence of Universal Health Insurance Coverage could increase household welfare, particularly, in their consumption. However, there is disagreement in the discussion of this topic. This study examines whether the Universal Health Insurance program in Indonesia could increase household consumption among self-employed citizens. Using household panel datasets about household consumption, household characteristics, and community characteristics for a large sample of Indonesian population over period 1995-2015, we find that the participation in this program has positive impact on household consumption. This paper divides the data into four waves, consisting of five consecutive years each. By using IV we found that the estimation is relatively stable in every wave, except in the periods between 2010-2015, when new participants in the programs suddenly jumped significantly.